2002
DOI: 10.1074/jbc.m206981200
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Helicase, DDX1, Interacting with Poly(A) RNA and Heterogeneous Nuclear Ribonucleoprotein K

Abstract: Heterogeneous nuclear ribonucleoprotein K (hnRNP K) is a multifunctional protein known to be involved in the regulation of transcription, translation, nuclear transport, and signal transduction. To systematically obtain insight into mechanisms of hnRNP K activities, we set out to identify protein factors that interact with hnRNP K by using glutathione S-transferase-hnRNP K affinity chromatography followed by liquid chromatography/mass spectrometry/mass spectrometry analysis. Several partner proteins in the K56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 39 publications
1
57
2
Order By: Relevance
“…In a previous study, recombinant DDX1 was unable to unwind RNA-RNA duplexes containing either 10 or 14 bp of complementary sequence (16). Here we have shown that DDX1 can unwind both RNA-RNA and RNA-DNA duplexes containing 29 bp of double-stranded structure in an ADP-dependent manner.…”
Section: Discussionmentioning
confidence: 85%
“…In a previous study, recombinant DDX1 was unable to unwind RNA-RNA duplexes containing either 10 or 14 bp of complementary sequence (16). Here we have shown that DDX1 can unwind both RNA-RNA and RNA-DNA duplexes containing 29 bp of double-stranded structure in an ADP-dependent manner.…”
Section: Discussionmentioning
confidence: 85%
“…Brcc3 is a subunit included in BRCA complexes that are involved in DNA repair [19]. Ddx1 is a putative RNA helicase that binds hnRNP [20] and Commd3 is assumed to block NF-kB function via inhibiting access of NF-kB to chromatin [17]. We also quantified the expression level of genes that have been reported to be involved in neural crest/tube defects, and found that 3 genes, EphrinA5 [21], Folbp1 [22], and Sox10 [23], were differentially expressed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that hnRNP K, YB-1, and DDX1 form complexes with the Cat-1 IRES (see Table S2 in the supplemental material). These proteins are known to interact with one another (7,60,75) and with hnRNP L and PTB (13,29,40). The recruitment of the ribosome may involve interactions of these proteins with ribosome-associated proteins such as RACK1 (59).…”
Section: Discussionmentioning
confidence: 99%